Hypothalamus metabolomic profiling to elucidate the tissue-targeted biochemical basis of febrile response in yeast-induced pyrexia rats. (25th April 2015) - Liu, Haiyu; Zhang, Li; Zhao, Baosheng; Zhang, Zhixin; Qin, Lingling; Zhang, Qingqing; Wang, Qing; Lu, Zhiwei; Gao, Xiaoyan
Highlights: The hypothalamus-targeted metabolomics were studied in the paper. Seventeen potential biomarkers related to yeast-induced fever were identified. The disturbed metabolism of metabolites can be speculated in yeast-induced fever. Abstract: In the previous reports regarding thermoregulation, the hypothalamus is thought to be the primary centre in the central nervous system for controlling the body temperature. However, to date, there has not been sufficient evidence to reveal its thermoregulatory mechanism. In the current study, we utilised a tissue-targeted metabolomics strategy to elucidate the underlying biochemical mechanisms of thermoregulation in the fever process by analysing the global metabolic profile of the hypothalamus in yeast-induced pyrexia rats. Data acquisition was completed using the HPLC-LTQ–Orbitrap/MS in both positive and negative ion mode. Principal component analysis was used to observe the cluster characteristics between the control group and the pyrexia group. Potential biomarkers were screened using orthogonal partial least-squares-discriminant analysis. Seventeen potential biomarkers were identified in the hypothalamus samples to discriminate the control and pyrexia groups, including amino acids, nucleic acids, vitamins, carbohydrates, and phospholipids. As a result, purine metabolism was enhanced pronouncedly, and perturbation of lipid metabolism was also observed. Meanwhile, amino acid metabolism and energy metabolism were also activated significantly. In conclusion, the study indicated that hypothalamus-targeted metabolomics could provide a powerful tool to further understand the pathogenesis of febrile response.